Dual-phase high-entropy (FeCoNiZn)xV2Oy oxides with promising microwave absorption properties. Issue 24 (15th December 2022) - Yan, Zhikai; Li, Depeng; Zhang, Xin; Men, Qiaoqiao; Fan, Bingbing; Guan, Li; Guo, Xiaoqin; Zhang, Rui; Zhao, Biao
Abstract: Dual-phase high entropy oxide (HEO) ceramics (FeCoNiZn)x V2 Oy were prepared using a simple sintering process. Vanadium oxide was selected due to the characteristics of reduction ability and multiphase transformation under different conditions. The crystal structure, microstructure, elemental chemical state, magnetic property and microwave absorption (MA) properties of HEO ceramics were studied. The results show that the two-phase structure is spinel phase and vanadate phase, and there are oxygen vacancies in the samples. Magnetic properties can be promoted with high content of spinel phase. Lots of oxygen vacancies were found in the sample sintered at 900 °C, which exhibited good MA ability. The minimum reflection loss (RL) of −36.5 dB was obtained at 10.72 GHz with a thickness of 2.2 mm, while the effective bandwidth reached 2.77 GHz. Large number of oxygen vacancies can speed up the migration of electrons or ions, thereby improving the dielectric loss capability.